2016
DOI: 10.18203/2320-6012.ijrms20160513
|View full text |Cite
|
Sign up to set email alerts
|

Study of altered platelet morphology with changes in glycaemic status

Abstract: Background: Diabetes is a pandemic causing very high morbidity and mortality due to its complications which are a result of micro and macro angiopathy. Platelets play a key role in the vascular complications. These complications are attributed to platelet activation which can be recognised by an increase in platelet volume indices (PVI) including mean platelet volume (MPV) and platelet distribution width (PDW). Platelet indices can be potentially useful surrogate markers for the early diagnosis of thromboembol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 8 publications
2
8
1
Order By: Relevance
“…This large study of adults with T2DM reported that duration of diabetes was positively correlated with PDW and MPV. That study also reported positive correlation between PDW and HbA1c [3]. We observed no statistically significant difference in PDW between our study groups.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This large study of adults with T2DM reported that duration of diabetes was positively correlated with PDW and MPV. That study also reported positive correlation between PDW and HbA1c [3]. We observed no statistically significant difference in PDW between our study groups.…”
Section: Discussionsupporting
confidence: 68%
“…Mean platelet volume (MPV) is a marker of platelet function and activation. MPV and platelet distribution width (PDW) can be used as markers in the early diagnosis of diabetic complications in patients with type 2 diabetes mellitus (T2DM) [3]. Plateletcrit (PCT) levels are defined as an independent marker of vascular changes, particularly in the coronary arteries.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies showed a mean MPV lesser than the present study whereas one study conducted by Sharma M et al (22) showed higher MPV than our study (table 2,3). Among controls, 46 out of 70 patients (65.7%) had MPV of < 10.5 fL and 24 out of 70 (24.2%) had MPV of ≥10.5 fL with a mean of 10.173±0.7134.…”
Section: Complicationscontrasting
confidence: 79%
“…However, no statistical correlation was noted between MPV and age, duration of DM, FBS; PDW and age, duration of DM, FBS; P-LCR and age, duration of DM, FBS. (15) 10.43±1.03 9.2±0.91 0.001 Sharma M et al (22) 17.60±2.04 9.93±0.64 <0.001 Khode V et al (23) 9.54 ± 0.9 9.21 ± 0.6 0.018 Present study 11.377±1.1969 10.173±0.7134 0.0001 …”
Section: Inclusion Criteria: Diabetic Patients With Vascular Complicamentioning
confidence: 55%
“…This suggests the association between the platelet size and diabetic vascular complications, thus indicating alterations in MPV reflect the state of thrombogenesis. [10] PDW can directly measure the variability of platelet size. Increased endothelial damage is seen in diabetes mellitus, which reduces the survival of platelets and increases turnover of younger platelets.…”
Section: Discussionmentioning
confidence: 99%